A Mystery of the Global Surplus and its Ramification - Malovic, Marko G (Industrija, 2013)
This paper deals with phenomenon of the increasingly indicative global imbalances and lagging genesis of balance of payments (BoP) accounting in an attempt to accommodate the ongoing mutation of international trade and finance. Namely, although BoP of the world as a whole should be zero since international trade in goods, services and financial assets ought to be a zero-sum game, our planet apparently runs a non-negligible and rising BoP surplus, projected to reach 1% of global GDP by 2015! To make the puzzle more bizarre, IMF statistics up until 2004 had recorded a persistent BoP deficit for the entire globe, which P. Krugman dubbed “The Mystery of the missing Surplus”. Well, surplus is back with the vengeance – while this paper tries to make sense of the phenomenon and pinpoint both its determinants and likely economic consequences. In conclusion, it appears that 1) during international financial crises quality and accuracy of the BoP statistics worsens worldwide, 2) net global imbalances may still be much smaller than we commonly believe, 3) true culprits may not be our usual suspects, 4) gross trade exhibits stark differences once confronted with decomposed value-added net exports and imports free of double counted processed exports and indirect exporting, 5) also, deliberate misreporting of cross-border investment proceeds as well as MNE’s transfer pricing practices may account for a relevant portion of registered global imbalances, and finally, 6) even the latest 6th edition of the IMF’s BoP and IIP Manual explicitly tackles but a few of the factors behind the returning surplus mystery.